القرابة الوراثية والصفات الإنتاجية لعشائر محلية من الحمص المزروع Cicer arietinum L.)) (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث على بذور سبع عشائر محلية من الحمص المزروع في سوريا وهي: المراكشي, الحوراني, الفوعي, الجبلي, الكردي, البلدي, الدرعوزي في مركز البحوث العلمية الزراعية في ادلب خلال موسمي الزراعة2001 /2002 -2002 /2003. انتخب 24 طرازاً وراثياً ذات خواص انتاجية جيدة وممثلة لهذه العشائر بمعدل ثلاثة طرز من كل عشيرة ماعدا عشيرة الفوعي والحوراني والكردي فقد انتخب اربعة طرزوراثية من كل منها، درست بعض الخواص الإنتاجية للطرز المنتخبة كما تم دراسة الإختلافات فيما بينها على المستوى الجزيئي. بين تحليل التباين (ANOVA) وجود فروقات معنوية بين الطرز المنتخبة في الخواص الإنتاجية. كما أظهرت التحاليل الجزيئية باستخدام مؤشرات المقاطع المحيطة بتوابع الـ DNA الدقيقة (الـSTMS) وجود تباينات وراثية بين وضمن العشائر المدروسة. استخدمت نتائج تحليل الـ DNA باستخدام الـ STMS في تقدير البعد الوراثي ونسب التشابه ما بين العشائر السبع وضمنها. Seeds of seven local populations of Chickpea (Marakchi, Horani, Fouei, Jabali, Kourdi, Baladi and Darouzi) were collected  from Syria and sowed during two season 2001 \ 2002-2002 \ 2003 at Agricultural Scientific Research Center in Idleb . Twenty-four genotypes characterized by good production  were selected for the analysis. theses genotypes were three of each population (except: Fouei, Horani and Kourdi were four genotypes). The yield characteristics of some of the produced genotypes as well as the differences among them at the particle level were studied. The analysis of variance (ANOVA) showed significant difference between those populations for all characters. The molecular analysis based on sequence-Tagged-microsatellite Site (STMS) demonstrated the presence of genetic variability among and within the different populations. Data obtained from DNA analysis were used in the estimation of genetic distance among and within the analyzed populations.